Beamforming, diversity, and interference rejection for multiuser communication over fading channels with a receive antenna array. - McCloud, M.L (IEEE Transactions on communications)
We consider M-ary communication with K users over a space diversity channel, consisting of a single transmit antenna for each user and multiple receive antennas. We examine two different flat fading models, namely, phase coherent wavefront fading and noncoherent element-to-element fading. In the case of wavefront fading, the fade is constant across the face of the receive antenna and we can associate an angle of arrival to the signal. We present a variation of the MUSIC algorithm for estimating this parameter and use it to form a spatial beam. In the case of noncoherent element-to-element fading, the fading path to each sensor is different (although possibly correlated) and no angle of arrival can be exploited for conventional beamforming. For each channel model, we develop several detection strategies which assume various amounts of prior information about the fading. We then consider blind extensions of these detectors based on subspace tracking, which do not require a prior model for the interfering users' signals.